Enterprise Evaluation: A New Opportunity for Public Health Policy. Issue 5 (September 2019) - Sherman, Mya; Covert, Hannah; Brown, Lisanne; Langhinrichsen-Rohling, Jennifer; Hansel, Tonya; Rehner, Timothy; Buckner, Ayanna; Lichtveld, Maureen
Abstract : Standard evaluation practice in public health remains limited to evaluative measures linked to individual projects, even if multiple interrelated projects are working toward a common impact. Enterprise evaluation seeks to fill this policy gap by focusing on cross-sector coordination and ongoing reflection in evaluation. We provide an overview of the enterprise evaluation framework and its 3 stages: collective creation, individual data collection, and collective analysis. We illustrate the application of enterprise evaluation to the Gulf Region Health Outreach Program, 4 integrated projects that aimed to strengthen health care in Louisiana, Mississippi, Alabama, and the Florida Panhandle after the Deepwater Horizon oil spill. Shared commitment to sustainability and strong leadership were critical to Gulf Region Health Outreach Program's success in enterprise evaluation. Enterprise evaluation provides an important opportunity for funding agencies and public health initiatives to evaluate the impact of interrelated projects in a more holistic and multiscalar manner than traditional siloed approaches to evaluation.